Simultaneous Near‐Surface Trace Doping and Surface Modifications by Gas–Solid Reactions during One‐Pot Synthesis Enable Stable High‐Voltage Performance of LiCoO2. Issue 30 (26th June 2022) - Tan, Xinghua; Zhao, Tingqiao; Song, Luting; Mao, Dongdong; Zhang, Yongxin; Fan, Zhengwei; Wang, Hanfu; Chu, Weiguo
Abstract: LiCoO2 (LCO) with a high theoretical capacity of 274 mAh g –1 can rarely achieve a high practical capacity even at an upper cutoff voltage of 4.6 V due to severe structural instability and interface side reactions. Herein, an in situ strategy of gas–solid modifications during synthesis is proposed to improve the performance of LCO using sulfocompound‐contained expanded graphite (EG) as templates. In situ generated SO2 gas from EG enables the Co‐coating of coherent spinel Li x Co2 O4 and Li2 SO4 and the trace doping of high‐valence S mainly in the near‐surface regions via its reactions with the precursors. The modified LCO possesses excellent structural reversibility, interfacial stability, slight dissolution of Co 2+, high diffusion coefficients of Li +, and low O 2p band top. This endows LCO with remarkably improved high‐voltage performance, 222 and 143 mAh g ‐1 at 0.1 and 20 C, respectively, and 88% capacity retention over 100 cycles at 1 C for LCO/Li half cells between 2.8 and 4.6 V, and 202 mAh g –1 at 1 C and 87% capacity retention over 1000 cycles between 2.8 and 4.5 V for LCO/graphite full cells. This study provides a unique, simple, and upscalable strategy for performance improvement of electrode materials. Abstract : A strategy of in situ gas–solid reactions during a one‐pot synthesis is proposed to improve the performance of LiCoO2 (LCO) by using sulfocompound‐contained expanded graphite (EG) as the template. Trace SO2 generated from EG enables the surface modification of Li2 SO4 and coherent spinel Li x Co2 O4 coatings and the near‐surface gradient doping of high‐valence S simultaneously, which result in remarkably improved high‐voltage performance of LCO.